Enhancing Firm Value: The Role of Managerial Ownership, Independent Commissioners, Audit Quality, and Corporate Social Responsibility - Puspitasari, Inggit Dwi; Rahayu, Sovi Ismawati (Santoso Academy Network, 2025)
This study aims to investigate the impact of managerial ownership, independent commissioners, audit quality, and corporate social responsibility (CSR) on firm value. It employs a quantitative research approach and focuses on a sample of companies within the primary consumer goods sector. The sampling method utilized is purposive sampling, resulting in a total of 23 companies. Secondary data, specifically the financial statements of these companies, were obtained from the official website of the Indonesian Stock Exchange (IDX). The analysis is conducted using multiple linear regression. The findings reveal that managerial ownership, audit quality, and CSR have a significant positive effect on firm value. In contrast, the variable of independent commissioners does not exhibit a significant impact on firm value. This study contributes to the existing literature by providing empirical evidence regarding governance and CSR practices that enhance firm value in emerging markets. It provides valuable insights for stakeholders seeking to enhance corporate governance mechanisms. From a managerial perspective, the results suggest that companies should enhance governance frameworks by increasing managerial ownership and ensuring that independent commissioners play an active role in strategic oversight. Additionally, prioritizing good audit quality is essential for improving transparency and fostering stakeholder trust.